Characterization of Donor Variability for γδ T Cell ex vivo Expansion and Development of an Allogeneic γδ T Cell Immunotherapy - Burnham, Rebecca E.; Zoine, Jaquelyn T.; Story, Jamie Y.; Garimalla, Swetha N.; Gibson, Greg; Rae, Aaron; Williams, Erich; Bixby, Lisa; Archer, David; Doering, Christopher B.; Spencer, H. Trent (Frontiers in Medicine, 2020)
Gamma delta (γδ) T cells recently emerged as an attractive candidate for cancer immunotherapy treatments due to their inherent cytotoxicity against both hematological and solid tumors. Moreover, γδ T cells provide a platform for the development of allogeneic cell therapies, as they can recognize antigens independent of MHC recognition and without the requirement for a chimeric antigen receptor. However, γδ T cell adoptive cell therapy depends on ex vivo expansion to manufacture sufficient cell product numbers, which remains challenging and limited by inter-donor variability. In the current study, we characterize the differences in expansion of γδ T cells from various donors that expand (EX) and donors that fail to expand, i.e. non-expanders (NE). Further, we demonstrate that IL-21 can be used to increase the expansion potential of NE. In order to reduce the risk of graft versus host disease (GVHD) induced by an allogeneic T cell product, αβ T cell depletions must be considered due to the potential for HLA mismatch. Typically, αβ T cell depletions are performed at the end of expansion, prior to infusion. We show that γδ T cell cultures can be successfully αβ depleted on day 6 of expansion, providing a better environment for the γδ T cells to expand, and that the αβ T cell population remains below clinically acceptable standards for T cell-depleted allogeneic stem cell products. Finally, we assess the potential for a mixed donor γδ T cell therapy and characterize the effects of cryopreservation on γδ T cells. Collectively, these studies support the development of an improved allogeneic γδ T cell product and suggest the possibility of using mixed donor γδ T cell immunotherapies.